Analisis Kinerja Induktor pada Main Pot untuk Proses Coating - Muhamad Dzaky Fadhilah; Choirul Anwar; Dede Ardi Rajab; Jatira; Irwan Suriaman (Sekolah Tinggi Teknologi Wastukancana, 2025)
The metal coating process plays an important role in improving the corrosion resistance and service life of products. One of its main components is the main pot, a refractory container that holds aluminum, zinc, and silicon alloys at high temperatures. The temperature stability of the coating fluid is highly dependent on the performance of the inductor as the main heat source. The problem encountered is that the inductor's capacity is not yet optimal in maintaining the operating temperature, thereby affecting the efficiency of the process and the quality of the coating results. This study aims to analyze the inductor's ability to maintain the main pot temperature, identify factors that affect heating efficiency, and provide recommendations for improving system performance. The methods used include measuring the liquid temperature, recording electrical power, and observing the decrease in coating volume. The results show that four inductors with a total capacity of 1800 kVA only meet about 20–23% of the energy requirements. The fluid temperature can be maintained in the range of 602–608 °C, but tends to decrease over time. The coating volume decreased by an average of 8.05–11.61% during five hours of operation. Increased power capacity and a periodic refill strategy are needed to maintain temperature stability and coating efficiency.